ChemInform Abstract: Diverse Natural Products from Dichlorocyclobutanones: An Evolutionary Tale. Issue 17 (April 2016) - Depres, Jean‐Pierre; Delair, Philippe; Poisson, Jean‐Francois; Kanazawa, Alice; Greene, Andrew E.
Abstract: Review: 73 refs.